EFFECT OF DIFFERENT IRRIGATION DEPTH ADJUSTMENT METHODS ON MAIZE YIELD COMPONENTS, GRAIN YIELD AND WATER USE EFFICIENCY - Chechi, Leonardo; Kuhn, Luan Junior; Fortuna, Vanderléia; de Almeida, Patricia Mara; Scariot, Maurício Albertoni; Camerini, Nerandi Luiz; Piazzetta, Hugo von Linsingen (IRRIGA, 2018)
As the water stress is one of the main causes for the low maize yield in Brazil, this study aimed to evaluate the yield components, grain yield and the water use efficiency of maize crop submitted to different methods of irrigation depth adjustment and validate the “Lâmina” spreadsheet to recommend irrigation depth in this crop. The treatments applied were: non-use of irrigation (control); irrigation depth adjustment provided by” Lâmina” spreadsheet (Lâmina); soil moisture equivalent to actual capacity of water in the soil at 55% of the total soil water capacity (55% RWC); and soil moisture equivalent to 100% of the field capacity (100% FC). The experimental design was a randomized block design with four replications, each experimental unit consists of a plot 3 meters wide and 3 meters long. The variables analyzed were total water applied, dry matter, ears per plant, kernel rows per ear, kernels per row, kernels per ear, one thousand kernels weight, grain yield and water use efficiency. Grain yields were similar between irrigated treatments, showing significant differences compared to the control. The Lâmina and 55% RWC showed the best results for water use efficiency and yield components. The Lâmina treatment used the least amount of water, with high yields, contributing to the rational water use in irrigated agricultural systems.